The role of Characeae in the communities of the vegetation class Potametea - Riccardo Guarino; Vincenzo Ilardi; Anna Maria Mannino; Angelo Troia (Palermo University Press, 2018)
The stonewort vegetation is commonly classified into the phytosociological class Charetea fragilis F. Fukarek ex Krausch 1964; however, the Characeae are not exclusively found in vegetation stands ascribed to this class but also in other habitat types. In our preliminary investigations, we draw the attention to the relationship between the classes Charetea fragilis and Potametea pectinati Klika in Klika & Novák 1941 in some Sicilian biotopes. In some cases, the Charetea vegetation is ecologically and spatially distinct, although close, from that referable to the Potametea. In some other cases, one or more species of Characeae are structurally intrinsic to the vegetation of Potametea: one example is offered by the pools next to the Maulazzo dam [Nebrodi Mts.], where Chara cfr. conimbrigensis A.G. Cunha enters the Groenlandietum densae Segal ex Schipper et al. in Schaminée et al. 1995, growing together with Groenlandia densa (L.) Fourr., Potamogeton natans L., Callitriche sp. pl. Another relevant case is the relationship of some Nitella species, such as N. capillaris (Krock.) J. Groves & Bull.-Webst. and N. opaca (C. Agardh ex Bruzelius) C. Agardh, with vegetation ascribed to the phytosociological alliance Batrachion fluitantis Neuhäusl 1959. In particular, the occurrence of the two different Nitella species goes along with two different species of Ranunculus subg. Batrachium, i.e. Ranunculus saniculifolius Viv. and R. aquatilis L., respectively, in two different sites. In these cases, phenology could be an important adaptive trait, with the Characeae developing earlier (between the end of winter and the beginning of spring) so to avoid the competition of the angiosperms that progressively develop during the spring months. Phenology is worth to be further investigated for the interactions not only between Characeae and angiosperms, but also between Characeae and other freshwater algae, such as the filamentous Spirogyra sp. pl., ascribed to the Zygnematales order of Charophyceae. However, this succession ...